Analisis Faktor-Faktor Maternal terhadap Kejadian Berat Bayi Lahir Rendah (BBLR) di Indonesia - Rizqika Aprilia Nugrahani; Dina Nur Anggraini Ningrum (Prodi Kebidanan Blora Program Diploma Tiga Poltekkes Kemenkes Semarang, 2025)
LBW is used as a parameter to assess the health status of the population widely. More than 20 million of the world's total births per year are LBW babies (15-20%). Indonesia itself has 6.1% of LBW cases by 2023, which is short of the global target. Therefore, this research aims to identify the maternal factors associated to LBW incidence in Indonesia, which will be used to develop evidence-based health policies. This research design used a cross-sectional design and data obtained from the Indonesia Health Survey (IHS) 2023, with 11.769 samples. Data were analyzed with descriptive analysis and a chi-square test. The results from this study showed that there was an association between CED (p-value 0,0001 < 0,05), hypertension (p-value 0,0001 < 0,05), and parity (p-value 0,002 < 0,05). On the other hand, variables that were not significantly associated with LBW because the p-value was more than 0.05 were maternal age, maternal education, and iron intake. This means that early detection of the pregnant woman's condition is necessary to prevent LBW.